2015
DOI: 10.7554/elife.08764
|View full text |Cite
|
Sign up to set email alerts
|

Differential inhibition onto developing and mature granule cells generates high-frequency filters with variable gain

Abstract: Adult hippocampal neurogenesis provides the dentate gyrus with heterogeneous populations of granule cells (GC) originated at different times. The contribution of these cells to information encoding is under current investigation. Here, we show that incoming spike trains activate different populations of GC determined by the stimulation frequency and GC age. Immature GC respond to a wider range of stimulus frequencies, whereas mature GC are less responsive at high frequencies. This difference is dictated by fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
24
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 48 publications
9
24
1
1
Order By: Relevance
“…PV-IN synapses onto new GCs are formed early (Song et al, 2013) but, as shown here, synaptic responses mature during several weeks, becoming increasingly stronger and faster. The slow IPSC kinetics exhibited by young synapses may well explain the hyperexcited neuronal behavior described previously in 4-week old GCs (Marin-Burgin et al, 2012;Pardi et al, 2015).…”
Section: Discussionsupporting
confidence: 68%
“…PV-IN synapses onto new GCs are formed early (Song et al, 2013) but, as shown here, synaptic responses mature during several weeks, becoming increasingly stronger and faster. The slow IPSC kinetics exhibited by young synapses may well explain the hyperexcited neuronal behavior described previously in 4-week old GCs (Marin-Burgin et al, 2012;Pardi et al, 2015).…”
Section: Discussionsupporting
confidence: 68%
“…Activity of individual GCs in response to glutamatergic inputs is primarily restrained by powerful GABAergic inhibition26353637. We used extracellular recording techniques to examine the influence of GABAergic inhibition on the GC responses to the cortical input, the perforant path (PP).…”
Section: Resultsmentioning
confidence: 99%
“…We used extracellular recording techniques to examine the influence of GABAergic inhibition on the GC responses to the cortical input, the perforant path (PP). As described previously3638, we first calibrated the input strength in individual rodent brain slices in the presence of two field-recording electrodes: one electrode placed in the molecular layer (ML), for field excitatory postsynaptic potentials (fEPSPs), and one in the GC layer (GCL), for population spikes (pSpikes) (Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, at this stage, immature neurons show higher excitability than mature granule neurons (Mongiat, Espósito, Lombardi, & Schinder, 2009). New neurons can generate action potentials even upon weak input (Marín-Burgin, Mongiat, Pardi, & Schinder, 2012), allowing them to respond to a much wider range of stimuli (Pardi, Ogando, Schinder, & Marin-Burgin, 2015). The expression of these distinct properties of adult-born neurons is transient and may serve as a major mediator for experience-dependent plasticity in the hippocampus.…”
mentioning
confidence: 99%